Comparative Serum Analyses Identify Cytokines and Hormones Commonly Dysregulated as Well as Implicated in Promoting Osteolysis in MMP-2-Deficient Mice and Children - Sarker, Hassan; Hardy, Eugenio; Haimour, Ayman; Karim, Mahmoud A.; Scholl-Bürgi, Sabine; Martignetti, John A.; Botto, Lorenzo D.; Fernandez-Patron, Carlos (Frontiers in Physiology, 2020)
Deficiency of matrix metalloproteinase 2 (MMP-2) causes a complex syndrome characterized by multicentric osteolysis, nodulosis and arthropathy (MONA) as well as cardiac valve defects, dwarfism and hirsutism. MMP-2 deficient (Mmp2-/-) mice are a model for this rare multisystem pediatric syndrome but their phenotype remains incompletely characterized. Here, we extend the phenotypic characterization of MMP-2 deficiency by comparing the levels of cytokines and chemokines, soluble cytokine receptors, angiogenesis factors, bone development factors, apolipoproteins and hormones in mice and humans. Initial screening was performed on an eight-year-old male presenting a previously unreported deletion mutation c1294delC (Arg432fs) in the MMP2 gene and diagnosed with MONA. Of eighty-one serum biomolecules analyzed, eleven were upregulated (>4-fold), two were downregulated (>4-fold) and sixty-eight remained unchanged, compared to unaffected controls. Specifically, Eotaxin, GM-CSF, M-CSF, GRO-α, MDC, IL-1β, IL-7, IL-12p40, MIP-1α, MIP-1β and MIG were upregulated and EGF and ACTH were downregulated in this patient. Subsequent analysis of five additional MMP-2 deficient patients confirmed the upregulation in Eotaxin, IL-7, IL-12p40 and MIP-1α, and the downregulation in EGF. To establish whether these alterations are bona fide phenotypic traits of MMP-2 deficiency, we further studied Mmp2-/- mice. Among 32 cytokines measured in plasma of Mmp2-/- mice, the cytokines Eotaxin, IL-1β, MIP-1α and MIG were commonly upregulated in mice as well as patients with MMP-2 deficiency. Moreover, bioactive cortisol (a factor that exacerbates osteoporosis) was also elevated in MMP-2 deficient mice and patients. Among the factors we have identified to be dysregulated in MMP-2 deficiency many are osteoclastogenic and could potentially contribute to bone disorder in MONA. These new molecular phenotypic traits merit being targeted in future research aimed at understanding the pathological mechanisms elicited by MMP-2 deficiency in children.